Organizational Citizenship Behavior Melalui Green Organizational Culture dan Mediasi Komitmen Organisasi - Indar, Sofyan Hamid; Asniwati, Asniwati; Baharuddin, Ida; Hadiningtyas, Eka Aussie; Latief, Fitriani (Jurnal Manajemen STIE Muhammadiyah Palopo, 2024)
Abstract The purpose of this study is to find out: the influence of green organizational culture on Organizational Citizenship Behavior; the influence of green organizational culture on organizational commitment; the influence of organizational commitment in mediating the relationship between green organizational culture and Organizational Citizenship Behavior. This study uses a quantitative research method. The population of this study is permanent employees of PT PLN (Persero) UIW Sulselrabar. The sampling technique is a saturated sample. So the total sample in this study is 115 people. Data analysis in this study was carried out using the Structural Equation Modelling (SEM) method to test the hypothesis that had been formulated. Each hypothesis was analyzed with the help of Partial Least Square (PLS) software version 3.0 to evaluate the relationship between the variables studied. The action activities include: distributing questionnaires, collecting, editing, and analyzing data and conclusions. The results of this study reveal that green organizational culture has a positive and significant influence on Organizational Citizenship Behavior (OCB). In addition, green organizational culture also has a positive and significant effect on organizational commitment. Furthermore, green organizational culture has a positive and significant influence on Organizational Citizenship Behavior through the mediation of organizational commitment.Keywords: Green Organizational Culture, Organizational Citizenship Behavior, Organizational CommitmentAbstrakTujuan penelitian ini adalah untuk mengetahui: pengaruh green organizational culture terhadap Organizational Citizenship Behavior; pengaruh green organizational culture terhadap komitmen organisasional; pengaruh komitmen organisasional dalam memediasi hubungan antara green organizational culture terhadap Organizational Citizenship Behavior. Penelitian ini menggunakan metode penelitian kuantitatif. Populasi dari penelitian ini adalah pegawai tetap PT PLN (Persero) UIW Sulselrabar. Teknik pengambilan sampel adalah sampel jenuh. Maka total sampel dalam penelitian ini adalah 115 orang. Analisis data dalam penelitian ini dilakukan menggunakan metode Structural Equation Modelling (SEM) untuk menguji hipotesis yang telah dirumuskan. Setiap hipotesis dianalisis dengan bantuan perangkat lunak Partial Least Square (PLS) versi 3.0 guna mengevaluasi hubungan antar variabel yang diteliti. Adapun kegiatan aksi mencakup: penyebaran kuesioner, pengumpulan, editing, dan analisis data serta kesimpulan. Hasil penelitian ini mengungkapkan bahwa green organizational culture memiliki pengaruh positif dan signifikan terhadap Organizational Citizenship Behavior (OCB). Selain itu, green organizational culture juga berpengaruh positif dan signifikan terhadap komitmen organisasional. Lebih lanjut, green organizational culture memberikan pengaruh positif dan signifikan terhadap Organizational Citizenship Behavior melalui mediasi komitmen organisasional.Kata Kunci: Green Organizational Culture, Organizational Citizenship Behavior, Komitmen Organisasional